Proposing a new construct to measure the effectiveness of brands operating in Social Networking Sites - Langaro, D.; Salgueiro, M.F.; Rita, P. (Proceedings of the 2nd . International Conference of Innovation and Entrepreneurship in Marketing and Consumer Behavior, 2015)
The current study was motivated by the increasing brand adoption of Social Networking Sites, like Facebook, in companies´ communication plans. Currently, the top 100 worldwide advertisers accumulate more than 1 billion users in their brand like pages. In view of this trend, it becomes important to propose a measure that captures the performance and effects of brands´ efforts in brand like pages. The present study addresses this research gap, proposing the construct of brand like page participation (BPP) and validating it. For that four phases were implemented and three studies were conducted. First, the construct domain was defined based on the literature review. Then, a qualitative study based on 10 interviews with Facebook users was implemented to further investigate the construct domain. Following that, an online survey with 203 respondents was used to assess the internal consistency and unidimensionality. Finally, the construct was validated for its ability to get reproduced with a new dataset including 575 valid responses. At this phase, collected data were submitted to confirmatory factor analysis (CFA), in order to check for reliability and convergence. Hence, a new construct is proposed and validated, targeted at offering managers and academics a clear tool to evaluate brands efforts in SNS and to estimate their business impact.